Silicate fiber doped battery slurry, preparation method thereof, silicon-based electrode and ion battery
By using silicate fibers to dopant battery slurry in lithium-ion batteries, the problem of electrode structure damage caused by volume changes during charging and discharging of silicon-based negative electrode materials is solved, and the cycle stability of the battery and the efficiency of the first circle of the Coulomb is improved. .
Patent Information
- Application Number
- CN202411655381.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
The silicon-based negative electrode material has severe volume changes during charging and discharging, resulting in low cycle stability and battery life, and low Coulomb efficiency in the first circle.
Silicate fiber doping battery slurry is used to enhance the electrode mechanical strength and lithium ion transmission path through interaction with silicon-based materials, binders, etc., and optimize the electrochemical performance.
It significantly improves the mechanical strength of the electrode and the efficiency of the first charging Coulomb, extends the service life of the battery, and maintains structural integrity and electrochemical performance after multiple charges and discharges at high magnifications.
Smart Images

Figure CN119481003A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of battery slurry synthesis and electrochemical technology, and relates to a battery slurry with high safety and low cost and a preparation method thereof, and in particular to a silicate fiber-doped battery slurry, a preparation method thereof, and a silicon-based electrode and an ion battery. Background Art
[0002] As the main battery for modern electronic devices and electric vehicles, the performance of lithium-ion batteries depends largely on the choice of electrode materials. Among the many negative electrode materials, silicon-based materials have attracted much attention due to their extremely high theoretical specific capacity, which is much higher than the currently widely used graphite negative electrode (about 372mAh / g). This means that silicon-based negative electrode materials have the potential to significantly improve the energy density of batteries and meet the market demand for higher endurance. However, there are some challenges in the practical application of silicon-based negative electrode materials. During the charging and discharging process, silicon-based particles will undergo drastic volume changes, resulting in pulverization and peeling of electrode materials, thereby reducing cycle stability and battery life. In addition, the side reactions of silicon-based materials with electrolytes are also relatively serious, forming a thicker solid electrolyte interface (SEI) film, consuming a large amount of lithium ions, and affecting the first cycle coulomb efficiency (ICE) of the battery.
[0003] Based on this, the present invention proposes a lithium-ion battery silicon-based negative electrode slurry that can effectively solve the above-mentioned problems. Summary of the invention
[0004] The purpose of the present invention is to provide a silicate fiber doped battery slurry and a preparation method thereof, as well as a silicon-based electrode sheet and an ion battery based on the slurry, in view of the shortcomings of poor structural stability and low first-cycle coulomb efficiency of silicon-based negative electrodes. The doping of silicate fibers significantly improves the mechanical strength of the electrode, so that the silicon-based electrode can withstand greater stress during the charge and discharge process. By optimizing the interaction between silicate fibers and silicon-based materials and binders, the fibers can improve the ICE of silicon-based electrodes. During the first charge process, more lithium ions can be effectively utilized, reducing energy loss. The slurry uses water as a solvent, and the preparation process is simple and environmentally friendly; the preparation process does not involve complex chemical reactions and is easy to mass produce; the raw materials used are low in price and highly safe. The silicon-based electrode sheet made of silicate fiber doped battery slurry has an 8% to 10% increase in coulomb efficiency after the first cycle, and can still maintain structural integrity and electrochemical performance after multiple charge and discharge cycles at high rates.
[0005] The objectives of the present invention are achieved through the following technical solutions.
[0006] A silicate fiber doped battery slurry is prepared by mixing silicon-based materials, conductive additives, binders and silicate fibers as raw materials with deionized water. The mass proportions of silicon-based materials, conductive additives, binders and silicate fibers in the raw materials are 60-95%, 0-20%, 4-20% and 1-10% respectively.
[0007] Preferably, the mass ratio of silicon-based material, conductive additive, binder and silicate fiber is 70:15:(7.5-12.5):(2.5-7.5).
[0008] Preferably, the silicon-based material is one or more of silicon powder, silicon-carbon powder, and silicon-oxygen powder.
[0009] Preferably, the silicate fiber is one or more of magnesium silicate fiber, calcium silicate fiber, sodium silicate fiber, and potassium silicate fiber.
[0010] Preferably, the silicate fiber is obtained by the following treatment:
[0011] S1: Disperse silicate fiber powder in deionized water, stir thoroughly after ultrasonication, filter the upper suspension after settling, and wash with deionized water for multiple times to obtain crude silicate fiber;
[0012] S2: subjecting the obtained crude silicate fiber to a hydrothermal acid treatment in an acidic solution to obtain the silicate fiber.
[0013] Preferably, the acidic solution is one or a mixed solution of citric acid, oxalic acid and hydrochloric acid.
[0014] Furthermore, the dosage ratio of the crude silicate fiber to the acidic solution is 1g:20mL~1g:80mL, and the hydrothermal conditions are to react at 120℃~200℃ in a reactor for 1~6h; a more preferred dosage ratio is 1g:40mL, and the hydrothermal reaction is carried out at 200℃ for 2h.
[0015] Preferably, the binder is a polymer containing polar groups, and the polar groups are one or more of hydroxyl, carboxyl and amino groups.
[0016] In the method for preparing the slurry, all raw materials may be directly mixed with deionized water, or the binder or the binder and silicate fibers may be pre-mixed with deionized water and then mixed with other raw materials.
[0017] A silicon-based electrode sheet, wherein the silicate fiber-doped battery slurry as described in any one of the above items is uniformly coated on a current collector.
[0018] An ion battery adopts the silicon-based electrode sheet as the negative electrode of the battery.
[0019] The present invention selects natural silicate fiber materials with high specific surface area and high mechanical hardness, and utilizes the Si-OH groups on its surface to form hydrogen bonds and mechanical interlocking with silicon-based materials, adhesives, etc., to form silicate fiber-doped battery slurry. These strong interactions can enhance the key role and stress transmission of the fiber, thereby achieving the effect of enhancing the strength of the material. The use of the silicate fiber-doped battery slurry can effectively solve the problem of electrode structure destruction caused by drastic volume changes in silicon-based negative electrode materials during charging and discharging. The interlayer channels of the silicate fiber can serve as lithium ion transmission channels, increase the migration rate of ions, reduce the excessive growth of the SEI film, and thus reduce the irreversible lithium ion loss during the first charging process.
[0020] Compared with the prior art, the present invention has at least the following beneficial effects:
[0021] (1) Maintaining the integrity of the electrode structure: The mechanical strength of the silicate fiber-doped battery slurry through the fiber-reinforced composite binder can withstand the volume changes of the silicon-based negative electrode material during the charge and discharge process, effectively preventing the damage to the electrode structure, thereby extending the service life of the battery. (2) Optimizing the transmission of lithium ions: Taking magnesium silicate fiber as an example, a layer of magnesium oxide octahedron is sandwiched between two layers of continuous silicon tetrahedrons, forming a "sandwich"-shaped special layered crystal structure unit. The unique layered crystal structure unit of silicate fiber provides a fast transmission path for lithium ions. This unique structural design significantly increases the migration rate of ions and helps to improve the charge and discharge performance of the battery. (3) Effectively control the excessive growth of the solid electrolyte interface (SEI) film and significantly improve the first-cycle coulomb efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the layered crystal structure of magnesium silicate fiber.
[0023] Figure 2 are the mechanical properties parameters of each sample.
[0024] Figure 3 The graphs are the cycle test results of each sample at a current density of 0.8 A / g.
[0025] Figure 4 is the lithium ion diffusion coefficient of each sample.
[0026] Figure 5 Scanning electron microscope images of magnesium silicate fibers before and after purification.
[0027] Figure 6 This is a scanning electron microscope image of magnesium silicate powder.
[0028] Figure 7 The scanning electron microscope images of each electrode sheet before and after cycling. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific embodiments. Unless otherwise specified, all raw materials in the present invention are commercially available, and all operating processes are conventional operations in the field.
[0030] The slurry used in the silicon-based electrode of the lithium-ion battery of the present invention is a silicate fiber-doped battery slurry prepared by mixing silicon-based materials, conductive additives, silicate fibers, and a binder with deionized water. According to a specific embodiment of the present invention, the preparation method thereof may be:
[0031] (1) Dispersing silicate fiber powder in deionized water, ultrasonically treating for 30 minutes and magnetically stirring for 30 minutes, allowing to settle for 24 hours, filtering the upper suspension, and repeatedly washing with deionized water for 3 times to obtain crude silicate fiber;
[0032] (2) subjecting the coarse silicate fibers in (1) to a hydrothermal acid treatment to obtain the silicate fibers;
[0033] (3) dissolving the binder in deionized water and stirring to form a binder solution;
[0034] (4) The silicon-based particles, the conductive agent, the binder solution and the silicate fibers are fully mixed in a mixer at a rate of 2500 rpm to obtain a silicate fiber-doped battery slurry.
[0035] In the present invention, the silicon-based material may generally be silicon-based particles, such as one or more of pure silicon powder, silicon-carbon powder, or silicon-oxygen powder.
[0036] In the present invention, the silicate is usually one or more of magnesium silicate, calcium silicate, sodium silicate and potassium silicate; the silicate fiber can be purchased directly, and the fiber length is about 10 to 30 microns and the width is about 1 to 3 microns. It has a distinct layered crystal structure, such as Figure 1 As shown, its appearance is Figure 5 shown.
[0037] In the present invention, the hydrothermal acid treatment is generally to add the crude silicate fiber into an acid solution, place it in a reactor, and perform hydrothermal treatment at 200°C for 2 hours. The acid solution can be one or a mixture of citric acid, oxalic acid, and hydrochloric acid. Through this treatment, a large amount of carbonate impurities in the silicate fiber can be removed, and the fiber can be evenly dispersed in water.
[0038] In the present invention, the binder is generally a polymer having polar groups such as hydroxyl, carboxyl, amino, etc., and can be one or more of polyvinyl alcohol, sodium alginate, sodium carboxymethyl cellulose, polyacrylic acid, etc.
[0039] In the present invention, the conductive additive is usually one or more of conductive carbon black, acetylene black, Super P, and carbon nanotubes.
[0040] When preparing silicon-based electrodes, the uniformly mixed silicate fiber-doped battery slurry can be coated on a current collector such as copper foil or foam copper, and the silicon-based electrode can be obtained after vacuum drying. The drying temperature is usually 80-120° C., and the drying time is usually 6-18 hours.
[0041] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments.
[0042] Example 1
[0043] S1) Magnesium silicate fiber pretreatment
[0044] The magnesium silicate fiber was dispersed in deionized water, ultrasonically treated for 30 minutes and magnetically stirred for 30 minutes, and then allowed to settle for 24 hours. The upper suspension was filtered and washed with deionized water for three times to obtain crude magnesium silicate fiber. The crude magnesium silicate fiber was subjected to hydrothermal acid treatment. The crude magnesium silicate fiber was mixed with a mixed acid solution at a solid-liquid ratio of 1:40 g / mL. The mixed acid solution consisted of a 1.5M hydrochloric acid solution and a 0.5M oxalic acid solution. The mixed acid solution was placed in a reactor and subjected to hydrothermal reaction in an oven at 200°C for 2 hours. The mixed acid solution was filtered and washed with deionized water for three times. The treated magnesium silicate fiber was dried with air at 60°C to obtain the treated magnesium silicate fiber.
[0045] S2) Synthesis of slurry A1
[0046] Dissolve 0.15g of polyacrylic acid in 9.85g of deionized water and stir for 3h to fully dissolve it to form a uniform binder solution with a mass concentration of 1.5%. Disperse 0.15g of treated magnesium silicate fiber in 0.15g of deionized water. Mix and stir the above two solutions for 10min to obtain a mixed binder. Mix the silica particles, conductive agent Super P, and mixed binder in a mixer at a rate of 2500rpm according to the mass ratio of dry matter after dehydration of 70:15:15. The resulting slurry is recorded as A1.
[0047] S3) Preparation of pole piece N1
[0048] The slurry A1 was evenly coated on the surface of the copper foil, and the solid coating mass was 1.1 mg / cm 2 , then dried in a vacuum drying oven at 100°C for 12 hours, cut into pieces, weighed, and the resulting electrode was marked as N1.
[0049] S4) Preparation of lithium-ion battery C1
[0050] 1.2M LiPF6 was dissolved in a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, and 25% by volume of fluoroethylene carbonate was added as an electrolyte; the prepared negative electrode plate N1 was transferred to an inert atmosphere glove box, and the plates N1, diaphragm and lithium plate were stacked in order, and then the electrolyte was injected for packaging to assemble into a lithium-ion half-cell. The resulting battery was recorded as C1.
[0051] Example 2
[0052] S1) Magnesium silicate fiber pretreatment
[0053] The preparation process is the same as S1 in Example 1.
[0054] S2) Synthesis of slurry A2
[0055] Dissolve 0.15g of polyacrylic acid (PAA) in 9.85g of deionized water and stir for 3h to fully dissolve it to form a uniform solution with a mass concentration of 1.5%. Disperse 0.075g of treated magnesium silicate fiber in 0.15g of deionized water, mix and stir the above two solutions for 10min to obtain a mixed binder. Mix the silica particles, conductive agent Super P, and mixed binder in a mixer at a rate of 2500rpm at a mass ratio of 70:15:15 after dehydration. The resulting slurry is recorded as A2.
[0056] S3) Preparation of pole piece N2
[0057] The manufacturing process is the same as that of pole piece N1, except that slurry A1 is replaced by A2.
[0058] S4) Preparation of lithium-ion battery C2
[0059] The manufacturing process is the same as that of the lithium-ion battery C1, except that the electrode N1 is replaced by N2.
[0060] Example 3
[0061] S1) Magnesium silicate fiber pretreatment
[0062] The preparation process is the same as S1 in Example 1.
[0063] S2) Synthesis of slurry A3
[0064] Dissolve 0.15g of polyacrylic acid (PAA) in 9.85g of deionized water and stir for 3h to fully dissolve it to form a binder solution with a mass concentration of 1.5%. Premix the silica particles, conductive agent Super P, and treated magnesium silicate fibers. Mix and disperse the premixed powder and binder solution in a mixer at 2500rpm. The mass ratio of the dry matter of the silica particles, conductive agent Super P, the aforementioned binder solution, and magnesium silicate fibers after dehydration is 70:15:10:5, and the resulting slurry is recorded as A3.
[0065] S3) Preparation of pole piece N3
[0066] The manufacturing process is the same as that of pole piece N1, except that slurry A1 is replaced by A3.
[0067] S4) Preparation of lithium-ion battery C3
[0068] The manufacturing process is the same as that of the lithium-ion battery C1, except that the electrode N1 is replaced by N3.
[0069] Example 4
[0070] S1) Calcium silicate fiber pretreatment
[0071] The production process is the same as S1 in Example 1, except that the magnesium silicate fiber is replaced by calcium silicate fiber.
[0072] S2) Synthesis of slurry A4
[0073] The production process is the same as S2 in Example 2, except that the magnesium silicate fiber is replaced by calcium silicate fiber.
[0074] S3) Preparation of pole piece N4
[0075] The manufacturing process is the same as that of pole piece N1, except that slurry A1 is replaced by A4.
[0076] S4) Preparation of lithium-ion battery C4
[0077] The manufacturing process is the same as that of the lithium-ion battery C1, except that the electrode N1 is replaced by N4.
[0078] Example 5
[0079] S1) Potassium silicate fiber pretreatment
[0080] The production process is the same as S1 in Example 1, except that the magnesium silicate fiber is replaced by potassium silicate fiber.
[0081] S2) Synthesis of slurry agent A5
[0082] The production process is the same as S2 in Example 2, except that the magnesium silicate fiber is replaced by potassium silicate fiber.
[0083] S3) Preparation of pole piece N5
[0084] The manufacturing process is the same as that of pole piece N1, except that slurry A1 is replaced by A5.
[0085] S4) Preparation of lithium-ion battery C5
[0086] The manufacturing process is the same as that of the lithium-ion battery C1, except that the electrode N1 is replaced by N5.
[0087] Example 6
[0088] S1) Magnesium silicate fiber pretreatment
[0089] The preparation process is the same as S1 in Example 1.
[0090] S2) Synthesis of slurry A6
[0091] Dissolve 0.3g of sodium alginate (SA) in 9.7g of deionized water and stir for 3h to fully dissolve it to form a uniform solution with a mass concentration of 3%. Disperse 0.15g of treated magnesium silicate fiber in 0.15g of deionized water. Mix and stir the above two solutions for 10min to obtain a mixed binder. Mix the silica particles, conductive agent Super P, and mixed binder in a mixer at a rate of 2500rpm according to the mass ratio of dry matter after dehydration of 70:15:15. The resulting slurry is recorded as A6.
[0092] S3) Preparation of pole piece N6
[0093] The manufacturing process is the same as that of pole piece N1, except that slurry A1 is replaced by A6.
[0094] S4) Preparation of lithium-ion battery C6
[0095] The manufacturing process is the same as that of the lithium-ion battery C1, except that the electrode N1 is replaced by N6.
[0096] Comparative Example 1
[0097] 0.15 g of polyacrylic acid (PAA) was dissolved in 9.85 g of deionized water and stirred for 3 h to fully dissolve it to form a binder solution with a mass concentration of 1.5%. Silica particles, conductive agent Super P, and PAA binder were mixed and dispersed in a mixer at 2500 rpm at a dry matter mass ratio of 70:15:15 after dehydration to obtain a slurry recorded as DA1.
[0098] After fully mixing, the materials are evenly coated on copper foil and vacuum dried at 100° C. for 12 h. The obtained electrode is denoted as DN1, and the obtained lithium-ion battery is denoted as DC1.
[0099] Comparative Example 2
[0100] 0.3 g of sodium alginate (SA) was dissolved in 9.7 g of deionized water and stirred for 3 h to fully dissolve it to form a uniform solution with a mass concentration of 3%. Silica particles, conductive agent Super P, and SA binder were mixed and dispersed in a mixer at 2500 rpm at a mass ratio of 70:15:15 of dry matter after dehydration to obtain a slurry recorded as DA2.
[0101] After fully mixing, the materials are evenly coated on copper foil and vacuum dried at 100°C for 12 hours. The obtained electrode is denoted as DN2, and the obtained lithium-ion battery is denoted as DC2.
[0102] Comparative Example 3
[0103] Dissolve 0.15g of polyacrylic acid (PAA) in 9.85g of deionized water, stir for 3h to fully dissolve it, and form a uniform solution with a mass concentration of 1.5%. Disperse 0.075g of directly purchased magnesium silicate powder in 0.15g of deionized water, mix and stir the above two solutions for 10min to obtain a mixed binder. Mix the silica particles, conductive agent Super P, and mixed binder in a mixer at a rate of 2500rpm according to the mass ratio of dry matter after dehydration of 70:15:15, and the resulting slurry is recorded as DA3.
[0104] After fully mixing, the materials were evenly coated on copper foil and vacuum dried at 100°C for 12 hours. The obtained electrode was denoted as DN3, and the obtained lithium-ion battery was denoted as DC3.
[0105] Comparative Example 4
[0106] Dissolve 0.3g of sodium alginate (SA) in 9.7g of deionized water and stir for 3h to fully dissolve it to form a uniform solution with a mass concentration of 3%. Disperse 0.15g of directly purchased magnesium silicate powder in 0.15g of deionized water. Mix and stir the above two solutions for 10min to obtain a mixed binder. Mix the silica particles, conductive agent Super P, and mixed binder in a mixer at a rate of 2500rpm according to the mass ratio of dry matter after dehydration of 70:15:15. The resulting slurry is recorded as DA4.
[0107] After fully mixing, the materials are evenly coated on copper foil and vacuum dried at 100°C for 12 hours. The obtained electrode is marked as DN4, and the obtained lithium-ion battery is marked as DC4.
[0108] Mechanical property test: Use nanoindentation technology to measure the hardness and elastic modulus of the binder materials in Example 2, Comparative Example 1, and Comparative Example 3 (the binder in Comparative Example 1, and the mixed binder in Example 2 and Comparative Example 3). The binder is dried into a thin film sample and placed in a nanoindenter. By controlling the indenter of a specific shape, the indenter is pressed into the sample surface at a certain loading rate until a preset depth is reached. After reaching the preset depth, the indenter begins to unload, and the changes in load and displacement are recorded at the same time. The hardness and elastic modulus of the material are calculated by analyzing the load-displacement curves during loading and unloading. Among them, due to the addition of silicate fibers ( Figure 2 ), the mixed binder used in Example 2 showed higher strength (0.05 GPa) and elastic modulus (7.3 GPa) than the binder in Comparative Example 1. In addition, compared with the mixed binder in Comparative Example 3, the use of silicate fiber relative to silicate powder can further improve the strength and elastic modulus, which also shows that the silicate fiber doped binder can effectively withstand the drastic volume change of silicon.
[0109] Cycle test: After the assembled button cell was left to stand for 12 hours, it was activated for 2 cycles at a current density of 0.03C (1C = 1600mAh / g), and cycled for 200 cycles at a current density of 0.5C. The test voltage range was 0.005 to 1.5V. The results are shown in Table 1 and Figure 3 The capacity retention rate of the battery for the Nth time = the discharge capacity for the Nth time / the discharge capacity for the first time × 100%. Among them, Example 2 showed 732 mAh g after 200 cycles. -1 The mass specific capacity and capacity retention rate of 80.88% ( Figure 3 ), the battery first efficiency is 69.26% (Table 1). It can be seen that the use of silicate fiber doped battery slurry can effectively improve the battery cycle capacity retention rate and first efficiency.
[0110] Lithium ion diffusion coefficient test: Warburg impedance data in the low-frequency region was obtained by electrochemical impedance spectroscopy, and the lithium ion diffusion coefficient was calculated based on Fick's law. After 100 cycles, the ionic conductivity of Example 1 was 9.44×10 -13 cm 2 / S, and that of Example 2 is 1.08×10 -12 cm 2 / S, and that of Example 3 is 7.69×10 -13 cm 2 / S, which are significantly higher than 2.76×10 -15 cm 2 / S and 5.88×10 -14 cm 2 / S( Figure 4). This shows that the silicate fiber is doped into the battery slurry in the present invention, and the interlayer structure of the silicate fiber can effectively improve the lithium ion diffusion coefficient.
[0111] Morphology characterization: Field emission scanning and transmission electron microscopy were used to observe the magnesium silicate fibers and magnesium silicate powder before and after treatment, and the N1, N2, DN1, and DN3 pole pieces before and after the cycle test. Figure 5 As shown in the figure, the impurities in the magnesium silicate fiber were significantly reduced after treatment, and the fiber was purified. Figure 6 As shown, magnesium silicate powder is in block form. Figure 7 As shown, the N1 and N2 pole pieces still maintain a smooth and crack-free morphology after 100 cycles, while obvious cracks are observed on the DN1 and DN3 pole pieces after cycles.
[0112] Table 1 First cycle coulombic efficiency and cycle capacity retention rate of each case
[0113]
Claims
1. A silicate fiber doped battery slurry, characterized in that: Its raw material composition is: The above raw materials are stirred and mixed with deionized water to obtain silicate fiber-doped battery slurry.
2. The silicate fiber-doped battery slurry according to claim 1, characterized in that: The silicon-based material is one or more of silicon powder, silicon-carbon powder and silicon-oxygen powder.
3. The silicate fiber-doped battery slurry according to claim 1, characterized in that: The silicate fiber is one or more of magnesium silicate fiber, calcium silicate fiber, sodium silicate fiber and potassium silicate fiber.
4. The silicate fiber-doped battery slurry according to claim 1, characterized in that: The silicate fiber is obtained by the following treatment: S1: Disperse silicate fiber powder in deionized water, stir thoroughly after ultrasonication, filter the upper suspension after settling, and wash with deionized water for multiple times to obtain crude silicate fiber; S2: subjecting the obtained crude silicate fiber to a hydrothermal acid treatment in an acidic solution to obtain the silicate fiber.
5. The silicate fiber-doped battery slurry according to claim 4, characterized in that: The acidic solution is one or a mixed solution of citric acid, oxalic acid and hydrochloric acid.
6. The silicate fiber doped battery slurry according to claim 4, characterized in that: The dosage ratio of the crude silicate fiber to the acid solution is 1g:20mL-1g:80mL, and the hydrothermal condition is to react at 120°C-200°C in a reaction kettle for 1-6h.
7. The silicate fiber-doped battery slurry according to claim 1, characterized in that: The binder is a polymer containing polar groups, and the polar groups are one or more of hydroxyl, carboxyl and amino groups.
8. The method for preparing silicate fiber-doped battery slurry according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: directly mixing all raw materials with deionized water, or pre-mixing the binder or the binder and silicate fiber with deionized water and then mixing with other raw materials.
9. A silicon-based electrode sheet, characterized in that: The silicate fiber-doped battery slurry as claimed in any one of claims 1 to 7 is uniformly coated on the current collector.
10. An ion battery, characterized in that: The silicon-based electrode sheet as claimed in claim 9 is used as the negative electrode of the battery.